Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Contribution of the slab fluids- melts to petrogenesis of adakitic rocks related to gold mineralization: Mo isotopic constraints - Shu-wen Li; Wen-liang Xu; Qun Yang; Yun-sheng Ren; Wu-shuang Zhang; Bin Wang; Kan Gao; Si-tong Chen; Yao-heng Fang; Hao-zhe Li; Tian-ci Liu; Xuan-mei Xue; et al. (Lithos, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Biallelic hexose-6-phosphate dehydrogenase variants cause mitochondrial dysfunction underlying Parkinson’s disease - Miao Zhao; Yuwen Zhao; Juan Huang; Yu Guo; Wenjun Yu; Haiyan Hou; Yilin Huang; Xinying Du; Yu Zhang; Mujun Xie; Zuowen Ren; Haoyu Guan; et al. (Science Bulletin, 2026)

Experimental and theoretical study on the ultimate bearing capacity of U-shaped steel-concrete composite cap beams - Heng Liu; Lin Xiao; Xing Wei; Xiang Li; Jian Ren; Huijun Wang (Engineering Structures, 2026)

Benzalkonium chlorides compromise oocyte maturation and developmental competence by disrupting mitochondrial function and the SIRT3-SOD2 antioxidant axis - Khienduc Lay; Dandan Zhang; Hui Wang; Mengchan Li; Yongteng Zhang; Qimei Xu; Bo Jia; ThiHien Nguyen; Chunhuan Ren; Xiaoyan Zhou; Heng Tang; Yinghui Ling; et al. (Animal Reproduction Science, 2026)

Speciation-dependent bioaccessibility of lead in e-waste dismantling soils: Synchrotron spectroscopy reveals molecular controls across physiological compartments - Jian Liu; Yi-Fan Li; Yi-Heng Wang; Dong-Xing Guan; Hao-Ran Guan; Yi-Ren Li; Xing-Mei Liu (Journal of Hazardous Materials, 2026)

Purification of high alkali coal: Insights into syngas production and nitrogen conversion mechanism - Linxuan Li; Qiangqiang Ren; Shaobo Yang; Shaobo Han; Ruifang Cui; Yuqian Heng; Yingjie Wang (Fuel, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

A new insight of size-dependent plastics particles kinetics with regarding of metabolomics effects in liver and kidney - Hongying Gao; Jing Li; Zehua Xu; Yiyang Duan; Bowen Su; Mengting Li; Banyun Zheng; Miaomiao Ren; Hao Chang; Heng Wang; Yi Lin; Heqing Shen (Environmental Pollution, 2025)

Effects of copper and zinc on three stages-anaerobic fermentation of organic wastes - Yingying Cai; Minhua Cheng; Xinxin Liu; Guangfei Qu; Hongmei Zou; Heng Li; Shiqiang Zhao; Nanqi Ren (Environmental Research, 2025)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Coal gasification-combustion system − Part I: Principle and nitrogen migration characteristics - Shaobo Yang; Qiangqiang Ren; Shaobo Han; Ruifang Cui; Yujie Hu; Yuqian Heng; Shilong Dong; Linxuan Li; Mengyin Gong; Chen Liang; Shuai Guo; Neng Fang; et al. (Fuel, 2025)

Experimental study on the evolution of inorganic composition during purification of high-alkali coal at different temperatures - Linxuan Li; Qiangqiang Ren; Shaobo Yang; Yingjie Wang; Shaobo Han; Ruifang Cui; Yuqian Heng (Fuel, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Microbial behavior drives structure and composition changes during bio-cake evolution and implications for membrane fouling mitigation - Yazhou Sun; Zedong Lu; Chaoran Liu; Xing Li; Zhiwei Zhou; Jiawei Ren; Chen Li; Heng Liang (Chemical Engineering Journal, 2025)

New insight of surface water disinfection by Fe2+-SPC: Important role of carbonate radical and the influence of carbonate/bicarbonate ions on free radicals balance - Zixiao Ren; An Ding; Xu He; Piotr Oleskowicz-Popiel; Guibai Li; Heng Liang; Huu Hao Ngo; Wei Qiu (Journal of Environmental Management, 2025)

Enhanced iodinated disinfection byproducts formation in iodide/iodate-containing water undergoing UV-chloramine sequential disinfection: Machine learning-aided identification of reaction mechanisms - Zhen-Ning Luo; Huan He; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Meng-Yuan Xu; Heng-Xuan Zhao; Zheng-Xiong Zheng; Ren-Jie Pan; Chen-Yan Hu; Chao Zeng; Mohamed Gamal El-Din; et al. (Water Research, 2025)

Assessment of eco-driving strategies on carbon emissions for hybrid vehicles through portable emissions measurement systems - Bo-wen Li; Zhi-heng Chen; Xing-hang Zhu; Zhe Zhang; Zhong-ren Peng; Hong-mei Zhao; Hong-di He (Atmospheric Pollution Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Insights into the role of choline in farmed fish diet: a short review - Heng Chu Ren; Zhi Li Ding; Shun Yang; Hui Fei (Aquaculture International, 2025)

Enhancing performance in gravity-driven membrane systems through pre-coating with aluminum-based flocs: Mechanism and energy saving analysis - Yazhou Sun; Zedong Lu; Xing Li; Shaozhu Wang; Jianyong Feng; Yanling Yang; Zhiwei Zhou; Jiawei Ren; Heng Liang (Journal of Environmental Management, 2025)

Fabrication of green xylose-based nanofiltration membrane with enhanced performance and chlorine resistance - Yumeng Xie; Jing Ren; Peng Liu; Junfeng Zheng; Zhaohuan Mai; Yanyan Liu; Xuewu Zhu; Xin Li; Daliang Xu; Heng Liang (Desalination, 2025)

Influence of S(IV) reduction on the reaction mechanisms and the generation of reactive oxygen species in B-Cu@Fe/PPS system - Xin Zhou; Yang Liu; Chuanshu He; Yuqi Zhang; Yujia Xiang; Jialong Yin; Shuai Yang; Zirong Li; Yue Yuan; Peng Zhou; Yi Ren; Heng Zhang; et al. (Journal of Hazardous Materials, 2024)

Refined implicit characterization of engineering geology with uncertainties: a divide-and-conquer tactic-based approach - Mingchao Li; Chuangwei Chen; Hui Liang; Shuai Han; Qiubing Ren; Heng Li (Bulletin of Engineering Geology and the Environment, 2024)
In engineering geology, a reasonable assessment of the spatial distribution of uncertainty in a region is vital in guiding research, saving money, and shortening the period. However, the traditional modeling process requires a lot of manual interaction, and the uncertainty of the geological model cannot be accurately quantified and utilized. This paper proposes a novel implicit geological modeling and uncertainty analysis approach based on the triangular prism blocks, which is divided into data point acquisition, ensemble model with divide-and-conquer tactic (EMDCT), uncertainty analysis, and post-processing. By employing machine learning algorithms, the EMDCT gives superior results for implicit modeling. The sensitivity analysis of the prediction results is further evaluated via information entropy. According to the distribution of uncertainty, supplementary boreholes are selected as additional knowledge to retrain the local components of the model to enhance their performances. The implicit modeling method is applied to real hydraulic engineering problems by employing the EMDCT, and the proposed model has obvious advantages in the implicit geological characterization. The overall accuracy in the working area with sparse boreholes reaches 0.922, which is 0.013 higher than the traditional method. By evaluating the distribution of uncertainty, an accuracy of 0.962 can be achieved, which is equivalent to reducing 10 boreholes.

Identification of particle distribution pattern in vertical profile via unmanned aerial vehicles observation - Zhi-Heng Chen; Bo-Wen Li; Bai Li; Zhong-Ren Peng; Hai-Chao Huang; Jun-Qi Wu; Hong-Di He (Environmental Pollution, 2024)

Maximizing potato tuber yields and nitrogen use efficiency in semi-arid environments by precision fertilizer depth application - Nanhai Zhang; Haiqiang Luo; Heng Li; Mingwei Bao; Enke Liu; Weixing Shan; Xiaolong Ren; Zhikuan Jia; Kadambot H.M. Siddique; Peng Zhang (European Journal of Agronomy, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Interfering TRIB3 protects the blood brain barrier through PI3K/Akt pathway to alleviate cerebral ischemia-reperfusion injury in diabetes mellitus mice - Heng-Jun Zhou; Xiao-Yi Wang; Li-Qing Wang; Jie-Sheng Zheng; Ren-Ya Zhan; Jian-Wei Pan (Chemico-Biological Interactions, 2024)

Responses of applied voltages on the archaea microbial distribution in sludge digestion - Yingying Cai; Heng Li; Guangfei Qu; Yinghui Hu; Hongmei Zou; Shiqiang Zhao; Minhua Cheng; Xiaomei Chu; Nanqi Ren (Chemosphere, 2023)

Selective elimination of sulfonamide antibiotics upon periodate/catechol process: Dominance of quinone intermediates - Shuai Yang; Yang Shi; Xinhao Wang; Yang Liu; Yi Ren; Wei Li; Heng Zhang; Xiaoqiang Dai; Weiyi Sun; Bo Lai (Water Research, 2023)

Higher ecological risks and lower bioremediation potentials identified for emerging OPEs than legacy PCBs in the Beibu Gulf, China - Li Zhang; Lingfang Ni; Heng Wang; Zhichao Zhang; Yichun Wu; Renming Jia; Junyu He; Zuhao Zhu; Haiyan Jin; Xing Ren; Dongdong Zhang (Environmental Research, 2023)

Experimental Study of Similar Simulated Material Proportioning for Small Scale Models - Yongjian Zhu; Peng Li; Ping Wang; Heng Ren; Chengcheng Mei; Mingxing Wei (Geotechnical and Geological Engineering, 2023)

Theoretical and Numerical Studies of Rock-Support Interaction by Considering Imperfect Rock-Lining Interface - Mingyang Ren; Xuyang Wu; Junkui Pan; Heng Liu; Ningjing Li (Geotechnical and Geological Engineering, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Removal of Bisphenol A via peroxymonosulfate activation over graphite carbon nitride supported NiCx nanoclusters catalyst: Synergistic oxidation of high-valent nickel-oxo species and singlet oxygen - Junjie You; Junyi Li; Heng Zhang; Mengfan Luo; Bo Xing; Yi Ren; Yang Liu; Zhaokun Xiong; Chuanshu He; Bo Lai (Journal of Hazardous Materials, 2023)

Research on the electrochemistry synergied cellulase enzymes strengthens the anaerobic fermentation of cow dung - Yingying Cai; Heng Li; Guangfei Qu; Junyan Li; Nanqi Ren; Hongmei Zou; Yinghui Hu; Jinhua Zeng (Environmental Science and Pollution Research, 2022)

A neuropsin-based optogenetic tool for precise control of Gq signaling - Ruicheng Dai; Tao Yu; Danwei Weng; Heng Li; Yuting Cui; Zhaofa Wu; Qingchun Guo; Haiyue Zou; Wenting Wu; Xinwei Gao; Zhongyang Qi; Yuqi Ren; et al. (Science China Life Sciences, 2022)

Experiment on the energy damage development process of water-saturated limestone under varied loading rates - Peng Li; Yongjian Zhu; Ping Wang; Heng Ren; Mingxing Wei; Xizhi Wang (Arabian Journal of Geosciences, 2022)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Experimental study on mechanical characteristics of unloaded damaged white sandstone before peak - Heng Ren; Yongjian Zhu; Ping Wang; Weijian Yu; Peng Li; Yuqun Zhang (Arabian Journal of Geosciences, 2020)

The expansion process of a Stellera chamaejasme population in a degraded alpine meadow of Northwest China - Fuyuan Gao; Kaiming Li; Chengzhang Zhao; Heng Ren; Xiaoying Nie; Dongyu Jia; Linfeng Li; Qingfeng Li (Environmental Science and Pollution Research, 2019)

Full genome sequence of the first bluetongue virus serotype 21 (BTV-21) isolated from China: evidence for genetic reassortment between BTV-21 and bluetongue virus serotype 16 (BTV-16) - Shaomin Qin; Heng Yang; Yixuan Zhang; Zhanhong Li; Jun Lin; Lin Gao; Defang Liao; Yingying Cao; Pengfei Ren; Huachun Li; Jianmin Wu (Archives of Virology, 2018)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

0.9% saline is neither normal nor physiological - Heng Li; Shi-ren Sun; John Q. Yap; Jiang-hua Chen; Qi Qian (Journal of Zhejiang University-SCIENCE B, 2016)

proBDNF Attenuates Hippocampal Neurogenesis and Induces Learning and Memory Deficits in Aged Mice - Jia Chen; Cheng-Ren Li; Heng Yang; Juan Liu; Tao Zhang; Shu-Sheng Jiao; Yan-Jiang Wang; Zhi-Qiang Xu (Neurotoxicity Research, 2016)

QTL Analysis for Grain Pentosans and Hardness Index in a Chinese 1RS.1BL × non-1RS.1BL Wheat Cross - Hong-Min Li; Heng Liang; Zong-Xiang Tang; Huai-Qiong Zhang; Ben-Ju Yan; Zheng-Long Ren (Plant Molecular Biology Reporter, 2013)

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)